Time in the therapeutic range, bleeding event, and their determinants in older patients with atrial fibrillation on warfarin in Ethiopia: multicenter cross-sectional study - Addisu, Zenaw Debasu; Demsie, Desalegn Getnet; Tafere, Chernet; Yazie, Taklo Simeneh; Endeshaw, Destaw; Tefera, Bereket Bahiru; Berihun, Malede; Beyene, Dessale Abate (Frontiers in Pharmacology, 2025)
BackgroundAtrial fibrillation (AF) poses significant thromboembolism and bleeding risks, especially in older adults. Warfarin continues to be a primary treatment option, and maintaining the Time in Therapeutic Range (TTR) is critical for ensuring its effectiveness. However, suboptimal TTR is associated with increased risks of stroke, bleeding, and mortality. Despite its importance, there is limited data on warfarin management in Ethiopian older adults with AF. Therefore, this study aimed to determine the TTR, bleeding events, and their determinants, in older patients with AF in Ethiopia receiving warfarin therapy.MethodIn this study, older patients with AF who were treated with warfarin and had follow-up visits between May 2021 and May 2024, and met the inclusion criteria, were included. Patients were categorized based on TTR into two groups: poor anticoagulation (TTR < 65%) and good anticoagulation quality (TTR ≥ 65%). Bivariate and Multivariate Logistic regression was performed to predict determinants of a TTR < 65% and bleeding events. Odds ratios with 95% confidence intervals (CIs) were calculated, and statistical significance was set at P < 0.05.ResultsIn this study, 384 patients with AF were included. Of this 53.4% were female. Of these 71% of patients had a TTR below 65%, 29% achieved ≥65%, with a median TTR of 45%. Bleeding events were reported by 13.5% of patients. Poor TTR was significantly associated with age (AOR = 1.199, 95% CI: 1.109–1.297), chronic kidney disease (AOR = 27.809, 95% CI: 7.57–101.76), and infrequent INR monitoring at 31–90-day intervals (AOR = 0.15, 95% CI: 0.004–0.051). Regarding determinants of bleeding events, Patients with diabetes mellitus had a 2.6-fold higher bleeding risk (AOR = 2.585, 95% CI: 1.069–6.250), and a CHA2DS2-VASc score ≥3 significantly increased bleeding risk compared to scores ≤2 (AOR = 7.562, 95% CI: 2.770–20.640).ConclusionThis study highlights suboptimal warfarin therapy among older Ethiopian patients with AF. Poor anticoagulation was associated with advanced age, chronic kidney disease, and infrequent INR monitoring, while diabetes mellitus and high CHA₂DS₂-VASc scores increased bleeding risks. Close monitoring and frequent INR checks are essential to improving outcomes.